1999
DOI: 10.1086/314899
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparumIsolates from Infected Pregnant Women and Children Are Associated with Distinct Adhesive and Antigenic Properties

Abstract: Plasmodium falciparum malaria during pregnancy is an important cause of maternal and infant morbidity and mortality. Accumulation of large numbers of P. falciparum-infected erythrocytes in the maternal blood spaces of the placenta may be mediated by adhesion of infected erythrocytes to molecules presented on the syncytiotrophoblast surface. In this study, isolates from placentas and peripheral blood of infected pregnant women and from children were tested for binding to purified receptors and for agglutination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
284
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(300 citation statements)
references
References 44 publications
16
284
0
Order By: Relevance
“…4 Furthermore, the VSA expressed by placental and CSA-adhering IEs (VSA PAM ) are antigenically completely distinct from other VSA. 5,6 These findings suggest that the reason why pregnant women become susceptible to P. falciparum malaria despite previously acquired protective immunity to the disease is not due to pregnancy-related immunosuppression as previously thought. Rather, the parasites causing PAM express VSA (VSA PAM ), which is not expressed by parasites infecting nonpregnant individuals and to which primigravidae consequently have no pre-existing immunity.…”
Section: Chondroitin Sulfate a And Hyaluronic Acid As Infected Erythrmentioning
confidence: 51%
“…4 Furthermore, the VSA expressed by placental and CSA-adhering IEs (VSA PAM ) are antigenically completely distinct from other VSA. 5,6 These findings suggest that the reason why pregnant women become susceptible to P. falciparum malaria despite previously acquired protective immunity to the disease is not due to pregnancy-related immunosuppression as previously thought. Rather, the parasites causing PAM express VSA (VSA PAM ), which is not expressed by parasites infecting nonpregnant individuals and to which primigravidae consequently have no pre-existing immunity.…”
Section: Chondroitin Sulfate a And Hyaluronic Acid As Infected Erythrmentioning
confidence: 51%
“…This hypothesis is supported by a recent study. 31 It demonstrated that parasites found in pregnant women were antigenically distinct from those common in children in the study area, and that the prevalence of agglutinating antibodies against these strains increased with gravidity. In hyperendemic areas, women usually acquire such antibodies during their first or second pregnancies.…”
Section: Discussionmentioning
confidence: 85%
“…35 In a given transmission area, parasites with specific receptors to placental tissue have an increased chance to establish themselves in the otherwise semi-immune pregnant host. [36][37][38] With successive pregnancies, immune mechanisms against these particular strains develop; infections become rarer and may increasingly comprise parasite genotypes also present in nonpregnant individuals. 38,39 If drug consumption propagates resistance in parasites able to adhere to placental ligands, it seems conceivable that this resistance is further selected within the group of pregnant women.…”
Section: Discussionmentioning
confidence: 99%